SIMULTANEOUS SELECTION IN COFFEE PROGENIES OF MUNDO NOVO BY SELECTION INDICES - Tassone, Guilherme Augusto Teixeira; Nadaleti, Denis Henrique Silva; Carvalho, Gladyston Rodrigues; Pereira, Fernanda Aparecida Castro; Andrade, Vinícius Teixeira; Botelho, César Elias (Coffee Science - ISSN 1984-3909, 2019)
Coffee cultivars that are better adapted and more productive can help reduce production costs and make coffee cultivation more profitable. The Mundo Novo cultivar has stood out as one of the most productive cultivars of Coffea arabica L. Therefore, the aim of this work was to select Mundo Novo progenies with high bean yield capacity and with other agronomic characteristics of interest. We evaluated the bean yield, seed size, plant height, upper and lower canopy diameter, stem diameter, and plant vigor of 24 F4 progenies and one check cultivar. The experimental design consisted of a randomized complete block design with three replications and experiments were carried out in two sites: São Sebastião do Paraíso (SSP) and Três Pontas (TP), MG, Brazil. The mixed model approach was used to calculate the genotypic value for each progeny, after which the selective accuracy and genetic gain of the two best progenies in each trait were calculated. To summarize, the simultaneous selection index of Mulamba and Mock was used to select the two most promising progenies at each site. In general, the genetic gain was higher at SSP than at TP. In SSP, the most promising progenies were 1 [IAC376-2 (M. Novo) x IAC386-17 (M. Novo)] and 20 [IAC382-10 (M. Novo) x IAC388-20 (M. Novo)]. In TP, the most promising progeny was 22 [H1535/181 (M. Novo) x (S795) 1344/10/5], together with the check (Mundo Novo IAC379/19). The highest selection gain was expressed for bean size (the percentage of beans retained in sieve 17).